2014
DOI: 10.15252/embr.201438553
|View full text |Cite
|
Sign up to set email alerts
|

Transport activity and presence of ClC‐7/Ostm1 complex account for different cellular functions

Abstract: that the ClC-7 protein, even when lacking measurable ion transport activity, is sufficient for hair pigmentation and that the conductance of ClC-7 unc is harmful for neurons. Our in vivo structure-function analysis of ClC-7 reveals that both proteinprotein interactions and ion transport must be considered in the pathogenesis of ClC-7-related diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
73
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 31 publications
1
73
0
Order By: Relevance
“…Not surprisingly, several MIST1 targets are involved in vesicle and membrane trafficking from ER to Golgi to secretory granules: Copz2, Ufm1, Large2, Ostm1, Ttc7b, Pon3, Tmed6, and Qpctl (Cynis et al 2008;Lemaire et al 2011;Schilling et al 2011;Shtutman et al 2011;Nakatsu et al 2012;Schweikert et al 2012;Wang et al 2012;Weinert et al 2014). COPZ2, one of the coatomer protein complex members that has not been extensively characterized, has been described previously as a MIST1 target (Direnzo et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not surprisingly, several MIST1 targets are involved in vesicle and membrane trafficking from ER to Golgi to secretory granules: Copz2, Ufm1, Large2, Ostm1, Ttc7b, Pon3, Tmed6, and Qpctl (Cynis et al 2008;Lemaire et al 2011;Schilling et al 2011;Shtutman et al 2011;Nakatsu et al 2012;Schweikert et al 2012;Wang et al 2012;Weinert et al 2014). COPZ2, one of the coatomer protein complex members that has not been extensively characterized, has been described previously as a MIST1 target (Direnzo et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…COPZ2, one of the coatomer protein complex members that has not been extensively characterized, has been described previously as a MIST1 target (Direnzo et al 2012). OSTM1 is interesting in that it seems to be a key adaptor protein involved in trafficking of lysosomes and secretory granules (e.g., melanosomes) via interaction with microtubule-associated motors (Weinert et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of Ostm1 and ClC-7 appears to be critical for ClC-7 function in ion transport and Cl Ϫ /H ϩ exchange (15,16). Based on low ClC-7 levels in gl/gl mice, Ostm1 was proposed to protect ClC-7 from degradation (14).…”
mentioning
confidence: 99%
“…They proposed a model in which ClC-5 could actively transport protons into the endosomes under the favorable conditions present immediately after vesicle pinching off (high Cl − concentration in the endosomes and negative membrane potential) [55]. Another speculative possibility is that ClC-5 could indirectly regulate the activity of other endosomal transport proteins through an effect on Cl − levels in endosomes [54,61,62]. Similar difficulties exist in explaining the role of the related Cl − /H + antiporter ClC-7 in lysosomal physiology and in the process of osteoclast bone resorption [4,63].…”
Section: Clc-5 Physiological Rolementioning
confidence: 99%
“…In conclusion, the hypothesis of a role of ClC-5 that is independent of its transport properties is suggestive but currently not supported by experimental evidence. In this respect, it is interesting to note that very recently, an ingenious approach based on the investigation of knock-in mice harboring a mutation that render ClC-7 transport deficient while preserving its targeting has directly demonstrated that some of the ClC-7 cellular functions do not require ion transport [62]. A similar investigation on ClC-5 could greatly advance our understanding of its physiological role.…”
Section: Transport Independent Physiological Rolesmentioning
confidence: 99%